Meio ambiente do trabalho e o direito à saúde mental do trabalhador - Pereira, Andre Sousa (2018)
Official rates have demonstrated the steady increase in the number of cases related to workers mental disorders in the last decades, especially during the beginning of the twenty-first century, intensified by characteristics of the production model, then conformed by global competition. In those lines, much has been discussed about the relation of cause and effect present between the degradation of the work environment by psychosocial risks risen from this production model and the manifestation of such diseases, both in national and international Law. This dissertation proposes a positive and active legal reflection about such issue, considering the possible delineation of non-degrading work conditions, aimed at the construction of a working environment conducive to the promotion and development of the workers psychic well-being. Based on the normative force of the tutelary set of human rights, within which the humanistic postulates pertinent to the issue interact, it aims to identify the already existing causal links between the mental disorders and the psychosocial risks present in the postfordist economic activity. Certainly, the establishment of a work environment with different traits to the causal assumptions sedimented as contributions to the outbreak of mental disorders related to these occupational risks, besides conforming to the founding value of the right to healthy ambience, equally harmonizes itself with the social and environmental functions of the company, consisting in the indispensable condition to guarantee and promote the worker’s full right to health, an essential vector for effective human dignity.